In vitro cultivation of canine multipotent mesenchymal stromal cells on collagen membranes treated with hyaluronic acid for cell therapy and tissue regeneration - Wodewotzky, T. I. [UNESP]; Lima-Neto, J. F. [UNESP]; Pereira-Júnior, O. C. M. [UNESP]; Sudano, M. J. [UNESP]; Lima, S. A. F. [UNESP]; Bersano, P. R. O. [UNESP]; Yoshioka, S. A.; Landim-Alvarenga, Fernanda da Cruz [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2012)
Support structures for dermal regeneration are composed of biodegradable and bioresorbable polymers, animal skin or tendons, or are bacteria products. The use of such materials is controversial due to their low efficiency. An important area within tissue engineering is the application of multipotent mesenchymal stromal cells (MSCs) to reparative surgery. The combined use of biodegradable membranes with stem cell therapy may lead to promising results for patients undergoing unsuccessful conventional treatments. Thus, the aim of this study was to test the efficacy of using membranes composed of anionic collagen with or without the addition of hyaluronic acid (HA) as a substrate for adhesion and in vitro differentiation of bone marrow-derived canine MSCs. The benefit of basic fibroblast growth factor (bFGF) on the differentiation of cells in culture was also tested. MSCs were collected from dog bone marrow, isolated and grown on collagen scaffolds with or without HA. Cell viability, proliferation rate, and cellular toxicity were analyzed after 7 days. The cultured cells showed uniform growth and morphological characteristics of undifferentiated MSCs, which demonstrated that MSCs successfully adapted to the culture conditions established by collagen scaffolds with or without HA. This demonstrates that such scaffolds are promising for applications to tissue regeneration. bFGF significantly increased the proliferative rate of MSCs by 63% when compared to groups without the addition of the growth factor. However, the addition of bFGF becomes limiting, since it has an inhibitory effect at high concentrations in culture medium.
Keywords: Collagen scaffolds; Biomaterials; Hyaluronic acid; Mesenchymal stromal cells; Tissue engineering; Cell culture